Cataract complications study: an analysis of adverse effects among 14,520 eyes in relation to surgical experience - Aaronson Alexander; Viljanen Antti; Kanclerz Piotr; Grzybowski Andrzej; Tuuminen Raimo (AME PUBL CO, 2025)
Background: To evaluate the learning-curve in performing cataract surgery with respect to developments in technology and different teaching strategies by comparing the incidence of capsular bag-related complications to operator experience.Methods: A review of the registry of 14,520 cataract surgeries carried out at the Ophthalmology Unit of Kymenlaakso Central Hospital, Kotka, Finland, from August 8, 2009 to July 31, 2017.Results: We identified 144 cases with posterior capsule rupture and/or loss of capsular bag support (incidence 0.99% of all surgeries). The mean age of patients was 76.99.1 years and gender distribution ratio 29:71 male:female. Pseudoexfoliation syndrome (PXF; incidence 21%) and small pupil (incidence 14%) were over-represented in complication eyes, especially at the beginning of the study. Capsular bag-related complication rates were reported in 0.36% of surgeries for senior and 7.03% for resident surgeons at the beginning of the study, compared to 0.32% and 1.32%, respectively, at the end of the study. Best-corrected visual acuity at the final post-operative visit was 0.61 +/- 0.16 decimals at the beginning of the study, and 0.81 +/- 0.19 decimals at the end of the study. The mean number of post-operative visits was 4.3 +/- 2.7 and did not show trend over the study period.Conclusions: Real-world evidence suggests PXF and small pupil as significant risk factors in cataract surgery. A gradual decline in the rate complications was noted with increasing surgical experience, also among residents over the follow-up period.